How do health content creators perform well? An integration research of short video and livestream behaviors - Liu, Jing; Ye, Qing; Wu, Hong; Ma, Rongyang; Guo, Shanshan; Long, Han (Frontiers in Public Health, 2024)
content, and advertising content on both short-term and long-term performance. The moderation effects of the creator's occupation and certification type were also analyzed.Results: Our form-level analysis revealed that health creators' behaviors in short videos and livestreaming play distinct roles in their performance. Livestreaming behaviors resulted in short-term economic returns, while short video behaviors had a more significant effect on follow-ups, which are often viewed as long-term, more sustainable performance indicators. Content-level analysis showed that content coverage and health knowledge content enhance long-term performance but do not increase short-term performance. Conversely, advertising content was found to be essential for securing short-term financial income. The study also identified that the creator's occupation and certification type moderate the impact of content on performance.Conclusion: This study integrates two media forms (short video and livestream), providing direct insights into the performance of health content creators in the realm of health education. Health content creators need to strategically balance their use of short videos and livestreaming to optimize both shortterm and long-term performance outcomes. Specifically, increasing content coverage and health knowledge can enhance long-term engagement, while incorporating advertising content is crucial for immediate financial gains.